Shielding cushioning foam for SMT welding

By penetrating stainless steel metal fibers into the silicone foam and using specific flame retardant modified mesoporous silica and other materials, the problem of softening, deformation or combustion of silicone foam at high temperatures is solved, and a high-performance shielding and buffer foam is achieved, with excellent electromagnetic shielding, heat resistance, flame retardant and low thermal conductivity.

CN118952811BActive Publication Date: 2025-03-18SUZHOU WANHE ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411022014.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-03-18
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

Existing silicone foams are prone to softening, deforming or burning at high temperatures, and cannot meet the strict requirements for heat resistance and flame retardancy during SMT welding.

Method used

A new type of shielding buffer foam is formed by penetrated through the stainless steel metal fibers and using materials such as methylvinyl silicone, platinum vulcanizer, hydrogen-containing silicone oil and flame-retardant modified short rod-shaped mesoporous silica. The foam enhances its flame retardant and thermal stability through fine molecular structure design and ammonium phosphate reaction.

Benefits of technology

It achieves the excellent electromagnetic shielding effect, heat resistance, flame retardant performance (UL94V-0) and low thermal conductivity of silicone foam, meeting the strict requirements for material performance during SMT welding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118952811B_ABST
    Figure CN118952811B_ABST
Patent Text Reader

Abstract

The present invention provides a shielding and buffering foam for SMT welding, which includes silicone foam, adhesive glue, and conductive cloth from bottom to top. The silicone foam is penetrated with stainless steel metal fiber. The silicone foam includes a first mixture and a second mixture. The mass ratio of the first mixture to the second mixture is 1:1-1.2. The first mixture includes: 100 parts of methyl vinyl siloxane and 0.2-2 parts of platinum vulcanizer; the second mixture includes: 15-30 parts of hydrogenated silicone oil and 10-20 parts of flame-retardant modified short rod-shaped mesoporous silica. The shielding and buffering foam for SMT welding of the present invention has the advantages of excellent electromagnetic shielding effect (≥90db), heat resistance, flame retardant performance (UL94V-0), low thermal conductivity, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to silica gel foam, which belongs to shielding and buffering foam for SMT welding. Background Art

[0002] Surface Mount Technology (SMT) is a key technology in electronic manufacturing and is widely used in the production of various electronic devices. In the SMT welding process, shielding and buffering materials are often required to ensure the stability and reliability of electronic components. These materials must not only have excellent buffering properties, but also have good heat resistance and flame retardancy to cope with high temperature environments and potential fire risks during welding.

[0003] Traditional shielding and buffering materials, such as foam plastics and rubber, have good buffering properties, but are obviously insufficient in terms of heat resistance and flame retardancy. Foam plastics are easy to melt or decompose at high temperatures, releasing harmful gases; rubber materials may age due to high temperatures, resulting in reduced buffering properties. Therefore, how to develop a material with excellent buffering properties, heat resistance and flame retardancy is an urgent problem to be solved in the current electronic manufacturing field.

[0004] As a new type of material, silicone foam has gradually attracted attention for its excellent elasticity, aging resistance and environmental protection properties. Silicone foam exhibits excellent thermal stability and low smoke and low toxicity in high temperature environments, making it an ideal shielding and buffering material. However, with the increasing complexity and integration of electronic equipment functions, the requirements for shielding and buffering foams in the SMT welding process have become more stringent. Especially in some high temperature environments or occasions with fire risks, the heat resistance and flame retardancy of shielding and buffering foams become particularly important. Existing silicone foam materials are prone to softening, deformation, and even burning at high temperatures, and cannot meet these stringent application requirements. Summary of the invention

[0005] The purpose of the present invention is to solve the problem in the prior art that the heat resistance and flame retardancy of silicone foam cannot meet the SMT welding requirements and thermal aging is prone to occur.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A shielding buffer foam for SMT welding, comprising silicone foam, adhesive, and conductive cloth from bottom to top, wherein the silicone foam is penetrated by stainless steel metal fibers, and the silicone foam comprises a first mixed material and a second mixed material, wherein the mass ratio of the first mixed material to the second mixed material is 1:1-1.2,

[0008] The first mixture includes: 100 parts of methyl vinyl siloxane and 0.2-2 parts of platinum vulcanizing agent;

[0009] The second mixture includes: 15-30 parts of hydrogen-containing silicone oil and 10-20 parts of flame-retardant modified short rod-shaped mesoporous silica.

[0010] Preferably, the preparation method of the silica gel foam comprises the following steps:

[0011] By weight, 126 parts of melamine and 90-120 parts of formaldehyde are dissolved in deionized water, and sodium hydroxide is used to adjust the pH of the mixed solution to 7.5-8.5. Too high alkalinity will accelerate further condensation reactions. The reaction is carried out at 5-20°C for 45-75 minutes to obtain a trihydroxy-formaldehyde-melamine intermediate. The reaction at a lower temperature can slow down the further condensation of the hydroxymethylation product, thereby helping to maintain it at the primary hydroxymethylamino stage. The mixed solution is then adjusted to a pH of 2-3 by sulfuric acid, 100-120 parts of diammonium hydrogen phosphate are added to react for 60-90 minutes, and vacuum dried to obtain a flame retardant precursor.

[0012] 100 parts of polyethylene glycol 2000 and 120-150 parts of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer are dissolved in an acidic solution with a pH of 0.1-1, and then 180-225 parts of tetraethyl orthosilicate are added dropwise, mixed evenly and reacted for 24-36 hours at 100-150°C and 0.5-0.6Mpa, washed with ethanol aqueous solution 2-3 times after centrifugation, vacuum dried for 2-3 hours, and calcined at 500-750°C for 5-10 hours to obtain short rod-shaped mesoporous silica.

[0013] 10 parts of short rod-shaped mesoporous silica and 10-12 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane were mixed, refluxed at 80-100° C. for 16-20 hours, filtered, washed with ethanol aqueous solution 2-3 times, and then vacuum dried for 6-8 hours to obtain modified short rod-shaped mesoporous silica.

[0014] 100 parts of modified short rod-shaped mesoporous silica and 80-150 parts of flame retardant precursor are dispersed in N,N-dimethylformamide, and subjected to ammonium phosphate reaction for 40-60 minutes. After washing with ethanol aqueous solution for 2-3 times, the mixture is vacuum dried for 2-4 hours to obtain flame retardant modified short rod-shaped mesoporous silica.

[0015] 0.2-2 parts of platinum vulcanizer are added to 100 parts of methyl vinyl siloxane and stirred evenly to form a first mixture, and 10-20 parts of flame retardant modified short rod-shaped mesoporous silica are added to 15-30 parts of hydrogenated silicone oil and mixed evenly to form a second mixture.

[0016] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1-1.2.

[0017] The mixed liquid is immediately poured into a pre-prepared mold, foamed and cured at 100-180° C., the foam is taken out of the mold, and stainless steel metal fibers are penetrated into the foam by a needle punching process to obtain the silicone foam.

[0018] In one or more embodiments, the viscosity of the methyl vinyl siloxane is 20000-50000 cps, and the vinyl content is 0.1-0.3%.

[0019] Preferably, the diameter of the stainless steel metal fiber is 50 μm. After the fiber penetrates, Z-axis conduction can be achieved.

[0020] Preferably, the mass content of hydrogen in the hydrogen-containing silicone oil is 1%-1.5%; and the viscosity is 20-40 cps.

[0021] Preferably, the platinum vulcanizing agent is Shenzhen Tyco C-25A.

[0022] Preferably, the conductive fabric is a plain woven conductive fabric to achieve XY axis conduction.

[0023] Preferably, the acupuncture density is 100-120 needles / cm 2 . Intensive acupuncture achieves all-round shielding.

[0024] Preferably, the conductive cloth is bonded to the silicone foam by using an adhesive using a hot pressing method.

[0025] In one or more embodiments, the foam is configured as a double-sided conductive cloth.

[0026] Compared with the prior art, the present invention has at least the following beneficial effects:

[0027] 1. The present invention uses N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to modify short rod-shaped mesoporous silica by amino modification. Subsequently, flame-retardant molecular chains are formed by condensation of melamine, formaldehyde and diammonium hydrogen phosphate under acidic conditions. The phosphate groups in these molecular chains are linked to the amino groups on the modified mesoporous silica through a phosphoric acid amination reaction, thereby fixing the flame-retardant molecules on the surface of the mesoporous silica. Finally, the flame-retardant modified mesoporous silica is incorporated into the cross-linking system of the silica gel foam to prepare a shielding buffer foam for SMT welding by foaming. The foam has the advantages of excellent electromagnetic shielding effect (≥90db), heat resistance, flame retardant performance (UL94V-0), and low thermal conductivity.

[0028] 2. The present invention ensures that a formaldehyde molecule is combined on each amino group to promote hydroxymethylation by accurately controlling the reactant ratio in the reaction of formaldehyde and melamine. Since the product of hydroxymethylation is easy to further form a stable resin structure through condensation reaction, the present invention reacts under an alkaline environment of relatively low concentration, which can effectively slow down the condensation rate. At the same time, the reaction is carried out under a temperature condition slightly lower than room temperature to keep the reaction in the primary stage of hydroxymethylamino. This control strategy helps to create conditions for the addition of diammonium hydrogen phosphate, so that it can effectively react with the hydroxyl (-OH) and amino (-NH2) in the trihydroxy-formaldehyde-melamine complex, thereby enhancing the performance of the final product.

[0029] 3. The present invention uses diammonium hydrogen phosphate, melamine, formaldehyde and short rod-shaped mesoporous silica as raw materials, and successfully synthesizes a new type of organic-inorganic composite toughening flame retardant through precise molecular structure design. The flame retardant exhibits a significant synergistic flame retardant effect, in which the combination of flame retardant molecular chains and short rod-shaped mesoporous silica can carbonize to form a protective carbon layer under high temperature conditions. In this process, the non-flammable inert gas produced by the decomposition of the phosphorus-nitrogen flame retardant molecular chains dilutes the necessary oxygen concentration, and the acidic substances such as phosphoric acid produced catalyze the formation of the carbon layer. The addition of short rod-shaped mesoporous silica not only enhances the thermal stability of the carbon layer, but also significantly improves the thermal stability of the overall material due to its highly ordered pore structure and thermal stability.

[0030] 4. Short rod-shaped mesoporous silica can form more effective mechanical interlocking in silicone foam due to its shape and high aspect ratio, thereby improving the overall mechanical strength and toughness of the material. This shape of silica can better withstand external stress, especially in high temperature environments, and help maintain the structural stability of the material.

[0031] 5. Short rod-shaped mesoporous silica, due to its highly ordered pore structure and high thermal stability, can significantly improve the overall thermal stability of the material when added to silicone foam. The pore structure of this mesoporous material not only forms a complex thermal resistance path in the silicone foam, but also effectively constructs a continuous heat conduction path. These heat conduction paths help to quickly disperse heat energy inside the material, thereby reducing the problem of local overheating. At the same time, the air layer contained in the pore structure of short rod-shaped mesoporous silica increases the resistance in the heat transfer process, reduces the heat flow rate, and effectively isolates heat energy, reducing the overall thermal conductivity of the material.

[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic structural diagram of the shielding and buffering foam for SMT welding of the present invention.

[0034] Reference numerals:

[0035] 1-conductive cloth, 2-adhesive glue, 3-silicone foam, 4-stainless steel metal fiber. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, they can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is just an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field. In the following examples, unless otherwise specified, concentration % refers to mass percentage; the substances used can be obtained commercially. The technical scheme of the present invention is further described below in conjunction with specific embodiments, but the present invention should not be limited to these embodiments, unless otherwise described, they can be replaced by other equivalent or alternative features with similar purposes. Unless otherwise described, each feature is just an example in a series of equivalent or similar features. The terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by ordinary technicians in the field.

[0037] The reagents used in the present embodiment and comparative examples are as follows. Those skilled in the art can select appropriate reagents for substitution, which can also achieve the limitations of the present invention. The following reagent selection is not used to limit the present invention.

[0038] The polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was purchased from J&K Scientific Ltd. with a trade name of P123 and a molecular weight of 5,800.

[0039] Tetraethyl orthosilicate was purchased from Hubei Chengfeng Chemical Co., Ltd.

[0040] N-(2-aminoethyl)-3-aminopropyltrimethoxysilane was purchased from Shanghai Nice Chemical Technology Co., Ltd.

[0041] Platinum curing agent was purchased from Shenzhen Tyco Co., Ltd., brand C-25A, about 0.95g / cm 3 .

[0042] Methylvinylsiloxane was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with a viscosity of 20,000-50,000 cps and a vinyl content of 0.1-0.3%.

[0043] The hydrogen-containing silicone oil was purchased from Shanghai Myrel Biochemical Technology Co., Ltd., with a hydrogen content of 1%-1.5% and a viscosity of 20-40 cps.

[0044] Figure 1 The schematic diagram of the structure of the shielding and buffering foam for SMT welding of the present invention is shown. The shielding and buffering foam for SMT welding includes, from bottom to top, a silicone foam 3, an adhesive 2, and a conductive cloth 1, and the silicone foam is penetrated by stainless steel metal fibers 4. It can also be set to have conductive cloth 1 on both sides. The foaming multiple of the silicone foam is 4.2 times. Those skilled in the art can adjust it according to customer needs.

[0045] Example 1

[0046] Preparation of shielding and buffering foam for SMT welding

[0047] 126g of melamine and 90g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 7.5 with sodium hydroxide, and the mixture was reacted at 5°C for 45min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2 with sulfuric acid, 100g of diammonium hydrogen phosphate was added to react for 60min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0048] 100 g of polyethylene glycol 2000 and 120 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 0.1, and then 180 g of tetraethyl orthosilicate was added dropwise, mixed evenly and reacted for 24 h at 100 ° C and 0.5 MPa, and then washed twice with ethanol aqueous solution with a mass ratio of 9:1, vacuum dried for 2 h, and calcined at 500 ° C for 5 h to obtain short rod-shaped mesoporous silica;

[0049] 10 g of short rod-shaped mesoporous silica was mixed with 10 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 80° C. for 16 h, filtered, washed twice with ethanol aqueous solution, and then vacuum dried for 6 h to obtain modified short rod-shaped mesoporous silica;

[0050] 100 g of modified short rod-shaped mesoporous silica and 80 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to ammonium phosphate reaction for 40 min. The mixture was washed twice with ethanol aqueous solution and then vacuum dried for 2 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0051] 0.2 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred evenly to form a first mixture, and 10 g of flame retardant modified short rod-shaped mesoporous silica was added to 15 g of hydrogenated silicone oil and mixed evenly to form a second mixture;

[0052] Slowly add the second mixture into the first mixture, stir quickly to avoid bubble generation, the mass ratio of the first mixture to the second mixture is 1:1;

[0053] The mixed liquid is immediately poured into the pre-prepared mold, foamed and solidified at 100°C, the foam is taken out of the mold, and a 50μm diameter stainless steel metal fiber is pierced through the foam to obtain silicone foam. The needle punching density is 100 needles / cm 2 .

[0054] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0055] Example 2

[0056] Preparation of shielding and buffering foam for SMT welding

[0057] 126g of melamine and 120g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 8.5 with sodium hydroxide, and the mixture was reacted at 20°C for 75min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 3 with sulfuric acid, 120g of diammonium hydrogen phosphate was added to react for 90min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0058] 100g of polyethylene glycol 2000 and 150g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 1, and then 225g of tetraethyl orthosilicate was added dropwise, mixed evenly and reacted for 36h at 150°C and 0.6Mpa, and then washed three times with 9:1 ethanol aqueous solution, vacuum dried for 3h, and calcined at 750°C for 10h to obtain short rod-shaped mesoporous silica;

[0059] 10 g of short rod-shaped mesoporous silica was mixed with 12 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 100° C. for 20 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 8 h to obtain modified short rod-shaped mesoporous silica;

[0060] 100 g of modified short rod-shaped mesoporous silica and 150 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to phosphate ammonium reaction for 60 min. After washing with ethanol aqueous solution for 3 times, the mixture was vacuum dried for 4 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0061] 2 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred evenly to form a first mixture, and 20 g of flame retardant modified short rod-shaped mesoporous silica was added to 30 g of hydrogenated silicone oil and mixed evenly to form a second mixture;

[0062] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.2.

[0063] The mixed liquid is immediately poured into the pre-prepared mold, foamed and solidified at 180°C, the foam is taken out of the mold, and a stainless steel metal fiber with a diameter of 50μm is pierced through the foam to obtain silicone foam. The needle punching density is 120 needles / cm 2 .

[0064] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0065] Example 3

[0066] Preparation of shielding and buffering foam for SMT welding

[0067] 126g of melamine and 100g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 8 with sodium hydroxide, and the mixture was reacted at 15°C for 60min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2.5 with sulfuric acid, 110g of diammonium hydrogen phosphate was added to react for 75min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0068] 100 g of polyethylene glycol 2000 and 135 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 0.5, and then 200 g of tetraethyl orthosilicate was added dropwise, mixed and reacted uniformly at 125°C and 0.55 MPa for 30 h, and then washed twice with an ethanol aqueous solution with a mass ratio of 9:1, vacuum dried for 2 h, and calcined at 600°C for 8 h to obtain short rod-shaped mesoporous silica;

[0069] 10 g of short rod-shaped mesoporous silica was mixed with 11 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 90° C. for 18 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 8 h to obtain modified short rod-shaped mesoporous silica;

[0070] 100 g of modified short rod-shaped mesoporous silica and 100 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to ammonium phosphate reaction for 50 min. After washing with ethanol aqueous solution twice, the mixture was vacuum dried for 3 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0071] 1.5 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred to form a first mixture, and 15 g of flame retardant modified short rod-shaped mesoporous silica was added to 25 g of hydrogenated silicone oil and mixed to form a second mixture;

[0072] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.

[0073] The mixed liquid is immediately poured into the pre-prepared mold, foamed and solidified at 150°C, the foam is taken out of the mold, and a stainless steel metal fiber with a diameter of 50μm is pierced through the foam to obtain silicone foam. The needle punching density is 110 needles / cm 2 .

[0074] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0075] Example 4

[0076] Preparation of shielding and buffering foam for SMT welding

[0077] 126g of melamine and 105g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 7.8 with sodium hydroxide, and the mixture was reacted at 10°C for 60min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2.3 with sulfuric acid, 105g of diammonium hydrogen phosphate was added to react for 65min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0078] 100 g of polyethylene glycol 2000 and 125 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 0.5, and then 200 g of tetraethyl orthosilicate was added dropwise, mixed and reacted uniformly at 115°C and 0.58 MPa for 28 h, and then washed three times with an ethanol aqueous solution with a mass ratio of 9:1, vacuum dried for 3 h, and calcined at 700°C for 8 h to obtain short rod-shaped mesoporous silica;

[0079] 10 g of short rod-shaped mesoporous silica was mixed with 10 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 85° C. for 18 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 7.5 h to obtain modified short rod-shaped mesoporous silica;

[0080] 100 g of modified short rod-shaped mesoporous silica and 135 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to phosphate ammonium reaction for 45 min. The mixture was washed twice with ethanol aqueous solution and then vacuum dried for 2.5 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0081] 1.5 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred to form a first mixture, and 16 g of flame retardant modified short rod-shaped mesoporous silica was added to 25 g of hydrogenated silicone oil and mixed to form a second mixture;

[0082] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.

[0083] Pour the mixed liquid into the pre-prepared mold immediately, foam and solidify at 100-180℃, take out the foam from the mold, and use the needle punching process to penetrate the 50μm diameter stainless steel metal fiber into the foam to obtain the silicone foam. The needle punching density is 120 needles / cm 2 .

[0084] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0085] Comparative Example 1

[0086] Preparation of shielding and buffering foam for SMT welding

[0087] 126g of melamine and 105g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 7.8 with sodium hydroxide, and the mixture was reacted at 10°C for 60min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2.3 with sulfuric acid, 105g of diammonium hydrogen phosphate was added to react for 65min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0088] 100 g of polyethylene glycol 2000 and 125 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 0.5, and then 200 g of tetraethyl orthosilicate was added dropwise, mixed and reacted uniformly at 115°C and 0.58 MPa for 28 h, and then washed three times with an ethanol aqueous solution with a mass ratio of 9:1, vacuum dried for 3 h, and calcined at 700°C for 8 h to obtain short rod-shaped mesoporous silica;

[0089] 10 g of short rod-shaped mesoporous silica was mixed with 10 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 85° C. for 18 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 7.5 h to obtain modified short rod-shaped mesoporous silica;

[0090] 100 g of modified short rod-shaped mesoporous silica and 135 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to phosphate ammonium reaction for 45 min. The mixture was washed twice with ethanol aqueous solution and then vacuum dried for 2.5 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0091] 1.5 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred evenly to form a first mixture, and 25 g of hydrogen-containing silicone oil was added to form a second mixture;

[0092] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.

[0093] Pour the mixed liquid into the pre-prepared mold immediately, foam and solidify at 100-180℃, take out the foam from the mold, and use the needle punching process to penetrate the 50μm diameter stainless steel metal fiber into the foam to obtain the silicone foam. The needle punching density is 120 needles / cm 2 .

[0094] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0095] Compared with Example 4, in Comparative Example 1, no flame-retardant modified short rod-shaped mesoporous silica was added to the second mixture, and the remaining operation steps and process flow were the same.

[0096] Comparative Example 2

[0097] Preparation of shielding and buffering foam for SMT welding

[0098] 126g of melamine and 105g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 7.8 with sodium hydroxide, and the mixture was reacted at 10°C for 60min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2.3 with sulfuric acid, 105g of diammonium hydrogen phosphate was added to react for 65min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0099] 10 g of spherical mesoporous silica was mixed with 10 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 85° C. for 18 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 7.5 h to obtain modified mesoporous silica;

[0100] 100 g of modified mesoporous silica and 135 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to phosphate ammonium reaction for 45 min. The mixture was washed twice with ethanol aqueous solution and then vacuum dried for 2.5 h to obtain flame retardant modified mesoporous silica.

[0101] 1.5 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred to form a first mixture, and 16 g of flame retardant modified mesoporous silica was added to 25 g of hydrogenated silicone oil and mixed to form a second mixture;

[0102] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.

[0103] Pour the mixed liquid into the pre-prepared mold immediately, foam and solidify at 100-180℃, take out the foam from the mold, and use the needle punching process to penetrate the 50μm diameter stainless steel metal fiber into the foam to obtain the silicone foam. The needle punching density is 120 needles / cm 2 .

[0104] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0105] Compared with Example 4, Comparative Example 2 is that the short rod-shaped mesoporous silica is replaced by mesoporous silica, and the remaining operating steps and process parameters are the same.

[0106] Comparative Example 3

[0107] Preparation of shielding and buffering foam for SMT welding

[0108] 126g of melamine and 50g of formaldehyde were dissolved in 1000ml of deionized water, and the pH of the mixed solution was adjusted to 9 with sodium hydroxide, and the mixture was reacted at 30°C for 60min to obtain a trihydroxy-formaldehyde-melamine intermediate, and the pH of the mixed solution was adjusted to 2.3 with sulfuric acid, 105g of diammonium hydrogen phosphate was added to react for 65min, and the mixture was vacuum dried at 120°C for 2h to obtain a flame retardant precursor;

[0109] 100 g of polyethylene glycol 2000 and 125 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer were dissolved in a hydrochloric acid solution with a pH of 0.5, and then 200 g of tetraethyl orthosilicate was added dropwise, mixed and reacted uniformly at 115°C and 0.58 MPa for 28 h, and then washed three times with an ethanol aqueous solution with a mass ratio of 9:1, vacuum dried for 3 h, and calcined at 700°C for 8 h to obtain short rod-shaped mesoporous silica;

[0110] 10 g of short rod-shaped mesoporous silica was mixed with 10 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, refluxed at 85° C. for 18 h, filtered, washed three times with ethanol aqueous solution, and then vacuum dried for 7.5 h to obtain modified short rod-shaped mesoporous silica;

[0111] 100 g of modified short rod-shaped mesoporous silica and 135 g of flame retardant precursor were dispersed in N,N-dimethylformamide, and subjected to phosphate ammonium reaction for 45 min. The mixture was washed twice with ethanol aqueous solution and then vacuum dried for 2.5 h to obtain flame retardant modified short rod-shaped mesoporous silica.

[0112] 1.5 g of platinum curing agent Shenzhen Tyco C-25A was added to 100 g of methyl vinyl siloxane and stirred to form a first mixture, and 16 g of flame retardant modified short rod-shaped mesoporous silica was added to 25 g of hydrogenated silicone oil and mixed to form a second mixture;

[0113] Slowly add the second mixture into the first mixture and stir quickly to avoid bubble generation. The mass ratio of the first mixture to the second mixture is 1:1.

[0114] Pour the mixed liquid into the pre-prepared mold immediately, foam and solidify at 100-180℃, take out the foam from the mold, and use the needle punching process to penetrate the 50μm diameter stainless steel metal fiber into the foam to obtain the silicone foam. The needle punching density is 120 needles / cm 2 .

[0115] Then, a hot press is used to bond the plain conductive cloth with adhesive and silicone foam, cooled, and cut into 3cm×3cm sizes.

[0116] Compared with Example 4, Comparative Example 3 adjusted the process parameters and raw material ratio of the flame retardant precursor, and the other operation steps and process flow were the same.

[0117] The shielding and buffering foams for SMT welding prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in Table 1.

[0118] The flame retardant performance test is carried out in accordance with UL94 "Test Methods for Flammability of Plastic Materials".

[0119] The high temperature resistance test method refers to GB / T3512-2001 "Hot air accelerated aging and heat resistance test for vulcanized rubber or thermoplastic rubber", and the test conditions are 280℃×96h (simulated reflow temperature 250℃-270℃)

[0120] Tensile strength and tensile elongation are tested according to GB / T528-2009

[0121] The thermal conductivity is tested according to GB / T10295-2008.

[0122] Table 1

[0123]

[0124]

[0125] It can be seen from Table 1 that since the flame retardant modified short rod-shaped mesoporous silica is not added to Comparative Example 1, its flame retardant performance does not meet the standard, and its mechanical properties and heat resistance are also significantly inferior to those of Example 4.

[0126] In Comparative Example 2, the short rod-shaped mesoporous silica is replaced by spherical or irregularly shaped mesoporous silica: its shape and highly ordered structure are not as good as those of the short rod-shaped mesoporous silica; its performance in thermal conductivity and thermal stability is reduced, and it cannot provide stronger mechanical interlocking. Therefore, the tensile strength and elongation of the silicone foam are reduced after the replacement.

[0127] In Comparative Example 3, since the reaction conditions in the synthesis of the flame retardant precursor were not controlled, most of the hydroxymethylated products underwent condensation reactions and could not better combine with diammonium hydrogen phosphate to form flame retardant molecular chains, resulting in reduced flame retardant effects.

[0128] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0129] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. For those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A shielding and buffering foam for SMT welding, characterized in that: From bottom to top, it includes silicone foam, adhesive, and conductive cloth. The silicone foam is penetrated by stainless steel metal fibers. The silicone foam includes a first mixed material and a second mixed material. The mass ratio of the first mixed material to the second mixed material is 1:1-1.

2. The first mixture includes: 100 parts of methyl vinyl siloxane and 0.2-2 parts of platinum vulcanizing agent; The second mixture includes: 15-30 parts of hydrogen-containing silicone oil and 10-20 parts of flame-retardant modified short rod-shaped mesoporous silica; The preparation method of the silica gel foam comprises the following steps: According to the weight components, 126 parts of melamine and 90-120 parts of formaldehyde are dissolved in deionized water, and the pH of the mixed solution is adjusted to 7.5-8.5 by sodium hydroxide, and the mixture is reacted at 5-20° C. for 45-75 minutes to obtain a trihydroxy-formaldehyde-melamine intermediate, and then the pH of the mixed solution is adjusted to 2-3 by sulfuric acid, 100-120 parts of diammonium hydrogen phosphate are added to react for 60-90 minutes, and vacuum drying is performed to obtain a flame retardant precursor; Dissolve 100 parts of polyethylene glycol 2000 and 120-150 parts of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer in an acidic solution with a pH of 0.1-1, then drop 180-225 parts of tetraethyl orthosilicate, mix evenly and react for 24-36 hours at 100-150° C. and 0.5-0.6 MPa, then wash with ethanol aqueous solution 2-3 times, vacuum dry for 2-3 hours, and calcine at 500-750° C. for 5-10 hours to obtain short rod-shaped mesoporous silica; Mix 10 parts of short rod-shaped mesoporous silica with 10-12 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, reflux at 80-100° C. for 16-20 hours, filter, wash with ethanol aqueous solution 2-3 times, and vacuum dry for 6-8 hours to obtain modified short rod-shaped mesoporous silica; Dispersing 100 parts of modified short rod-shaped mesoporous silica and 80-150 parts of flame retardant precursor in N,N-dimethylformamide, carrying out phosphate ammonium reaction for 40-60 minutes, washing with ethanol aqueous solution 2-3 times and vacuum drying for 2-4 hours to obtain flame retardant modified short rod-shaped mesoporous silica; 0.2-2 parts of platinum vulcanizing agent are added to 100 parts of methyl vinyl siloxane and stirred evenly to form a first mixture, and 10-20 parts of flame retardant modified short rod-shaped mesoporous silica are added to 15-30 parts of hydrogen-containing silicone oil and mixed evenly to form a second mixture; Slowly add the second mixture into the first mixture, stir quickly to avoid bubble generation, the mass ratio of the first mixture to the second mixture is 1:1-1.2; The mixed liquid is immediately poured into a pre-prepared mold, foamed and cured at 100-180° C., the foam is taken out of the mold, and stainless steel metal fibers are penetrated into the foam by a needle punching process to obtain the silicone foam.

2. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The viscosity of the methyl vinyl siloxane is 20000-50000 cps, and the vinyl content is 0.1-0.3%.

3. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The diameter of the stainless steel metal fiber is 50 μm.

4. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The mass content of hydrogen in the hydrogen-containing silicone oil is 1%-1.5%; the viscosity is 20-40cps.

5. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The platinum vulcanizing agent is Shenzhen Tyco C-25A.

6. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The conductive fabric is a plain woven conductive fabric.

7. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The acupuncture density is 100-120 needles / cm 2 .

8. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The conductive cloth is bonded to the silicone foam by a hot pressing method through an adhesive.

9. The shielding and buffering foam for SMT welding according to claim 1, characterized in that: The foam is configured as a double-sided conductive cloth.

Citation Information

Patent Citations

  • Silica gel foam and preparation method thereof

    CN109722038A

  • High-flame-retardant high-damping organic silicon foam material as well as preparation method and application thereof

    CN113502055A

  • Conductive silica gel foam and manufacturing process thereof

    CN117460241A

  • High-resilience conductive foam

    CN215183129U